Optical Waveguide Modelling Based On Scalar Finite Difference Scheme - Mohd. Kassim, Norazan; Mohammad, Abu Bakar; Ibrahim, Mohd. Haniff (Penerbit UTM Press, 2005)

(untitled)
A Numerical Method Based On Scalar Finite Difference Scheme Was Adopted And Programmed On MATLABÂ® Platform For Optical Waveguide Modeling Purpose. Comparisons With Other Established Methods In Terms Of Normalized Propagation Constant Were Included To Verify Its Applicability. The Comparison Results Obtained Were Proven To Have The Same Qualitative Behaviour. Furthermore, The Performances Were Evaluated In Terms Of Computation Complexity, Mesh Size, And Effect Of Acceleration Factor. Computation Complexity Can Be Reduced By Increasing The Mesh Size Which Will Then Produce More Error. The Problem Can Be Rectified By Introducing The Acceleration Factor, Successive Over Relaxation (SOR) Parameter. It Shows That SOR Range Between 1.3 And 1.7 Can Give Shorter Computation Time, While Producing Constant Value Of Simulation Results.